Cover Picture: Mechanochromic Luminescence Characteristics of Pyridine‐Terminated Chromophores in the Solid State and in a Poly(vinyl alcohol) Matrix (Chem. Asian J. 11/2014). Issue 11 (November 2014) - Kondo, Mizuho; Miura, Seiya; Okumoto, Kentaro; Hashimoto, Mayuko; Kawatsuki, Nobuhiro
<x xml:space="preserve">Abstract</x> Mechanoinduced changes in photoluminescence have attracted much attention in fundamental research and with respect to sensor applications. In their Full Paper on page 3188 ff., Mizuho Kondo, Nobuhiro Kawatsuki et al. prepared three pyridine‐terminated materials that change their photoluminescence color in response to a mechanical stimulus. In addition, patterning of the color change was successfully achieved using a dye‐dispersed polymer film. The polymer film can change the patterned color upon exposure to fuming acid as a result of a change in the electronic state of the compound.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>